Inheritance Of Shape And Kernel Color In Sweet Corn Using JM2 And JM4 Populations - Nugroho, Rizki Anjal Puji; Syukur, Muhamad; Suwarno, Willy Bayuardi (Department of Agronomy and Horticulture, IPB University, 2018)
Corn kernel is one of the most important characters that correlate with corn yield and quality. Sweet corn kernels can be distinguished by its color which is either yellow and white or pale yellow. Sweet corn breeding by crossing genotypes with different kernel colors will affect the inheritance pattern of kernel color. The aims of this research were to understand the inheritance pattern in sweet corn kernel color by crossing yellow and pale yellow color with red and purple corn kernels using qualitative and quantitative approaches. Genetic materials consisted of P1 (JM2 and JM4) and P2 (Red and Purple) and F1, F2, F3, and F1 reciprocals. P1 consists of JM2 and JM4 with flint shape with yellow and pale yellow color; P2 consists of Red and purple with non-yellow colored kernel and flint shape. The results showed maternal effect influenced the kernel color, but did not affect the kernel shape. Epistatic effects were found in kernel shape but it was co-dominant on kernel color inheritance. Broad-sense heritability values were high for all quantitative variables. Keywords : color, heritability, pale yellow, purple, red, shape